Contemporary points on monitoring the spatial organization of the human body in the process of physical education - Vitaliy Kashuba; Serhii Lopatskyi; Tetyana Prylutska (Kazimierz Wielki University, 2017)
Actuality. Disturbance of the spatial organization of the body is considered a pre-pathological state and can become one of the serious causes for the fixed disorders of the human musculoskeletal system. The peculiarity of monitoring spatial organization of the human body is that being a part of the state of somatic health monitoring, it is a technology that allows to observe, measure, evaluate and predict the parameters of the biogeometric profile of posture, support-spring characteristics of foot, functional status of the musculoskeletal system and features of human body in the process of physical education. Objectives of research: to provide information about peculiarities of the organizational and methodological basis of monitoring of the the human body spatial organization in the process of physical education. Results of research. During the process of monitoring the spatial organization of body, it is necessary to follow a number of general methodological rules, such as: consider the age-dependent features of the musculoskeletal system formation and development; consider the human motility ontogenetic features; consider adequately the topography of skeletal muscles for those engaged in sports; use informative methods of diagnostics of support-spring characteristics of the foot and biogeometric profile of human posture; use adequate methods and methodical techniques for the consistent prevention and correction of violations to the human body spatial organization by means of physical education. Conclusions. The peculiarity of monitoring spatial organization of the human body is that being a part of the state of somatic health monitoring, it is a technology that allows to observe, measure, evaluate and predict the parameters of the biogeometric profile of posture, support-spring characteristics of foot, functional status of the musculoskeletal system and features of human body in the process of physical education. The further research will be associated with the development of information and methodological system aimed on measuring the state of spatial organization of the human body in the process of physical education.